2015
DOI: 10.1097/dss.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Metastasis in Cutaneous Head and Neck Squamous Cell Carcinoma

Abstract: Because of the relatively low incidence of cervical lymph node metastases in patients with CSCC of the head and neck, SLNB for clinically N0 patients is not justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 11 publications
1
25
2
5
Order By: Relevance
“…Therefore, we did not perform SLNB aggressively for patients with T1 tumors. However, the present study and that of Silberstein et al . have demonstrated that harboring a T1 tumor is not risk‐free.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Therefore, we did not perform SLNB aggressively for patients with T1 tumors. However, the present study and that of Silberstein et al . have demonstrated that harboring a T1 tumor is not risk‐free.…”
Section: Discussioncontrasting
confidence: 85%
“…Therefore, the risk–benefit ratio should be considered when performing SLNB for cSCC, especially in elderly patients. Silberstein et al . justifies the policy of not performing SLNB for patients with low T stage head and neck cSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Множество проведенных исследований по изучению зако-номерностей роста и прогрессии опухолей кожи показа-ли, что чем выше содержание интегринов в опухоли, тем выше скорость ее инвазии и более выраженный ангиогенез [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Суть этих исследований заключалась в сравнении количества интегринов на разных клонах одной и той же опухоли, с определением скорости роста, инвазии и мета-стазирования каждого из клонов с последующим сравне-нием их между собой.…”
Section: влияние интегринов на прогрессию опухолей кожиunclassified
“…Суть этих исследований заключалась в сравнении количества интегринов на разных клонах одной и той же опухоли, с определением скорости роста, инвазии и мета-стазирования каждого из клонов с последующим сравне-нием их между собой. Результаты всех исследований были схожими: клоны, имевшие самый быстрый и злокаче-ственный рост, показывали наибольшую экспрессию ин-тегринов по сравнению с менее агрессивными вариантами тех же опухолей [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: влияние интегринов на прогрессию опухолей кожиunclassified